Therapeutic action of the evolocumab monoclonal antibody against PCSK9 proteins in LDL cholesterol modulation: systematic review - Ferreira, Mario Henrique Quim (2017)
Introduction: The hypercholesterolemia can lead to conditions such as acute myocardial infarction (AMI). However, cholesterol elevation is not always caused by poor diet habits and lifestyle; groups such as familial hypercholesterolemia (HF) have serum values increased by genetic alterations, and traditional dyslipidemic medications are not effective enough for these peoples. Objective: To compile and discuss the results obtained by the current literature that focuses on the evolocumab monoclonal antibody to decrease PCSK9 levels. Materials and methods: Systematic review of the results of tests done with humans over 19 years of age, published in the last 5 years in the English language, using the PubMed database. Results: 135 articles were found, and nine studies were selected by exclusion criteria. Discussion: Results demonstrated that the pharmacological power of the evolocumab antibody has a remarkable value compared to the usual therapies and placebo for patients who did not show great response to current therapies. Conclusion: This is a very recent study, which requires further research to show possible adverse reactions and interactions with other drugs. However, so far it has demonstrated a great advantage for future treatments because it occupies a place not previously filled by traditional pharmacology.